Impact of the Covid-19 confinement measures on telework in Italy - A qualitative survey - Angelo Moro (European Commission, Joint Research Centre (JRC), 2020)
This technical report presents the results of a qualitative survey conducted in April and May 2020 with 25 workers who worked in the telework regime - either full-time or part-time - during the lock-down period following the epidemic of Covid-19 in Italy. The report analyses the consequences of the transition to telework along three main dimensions: work organisation, job quality and worklife balance. We show how workers telework experience during the lock-down is extremely heterogeneous across the employment structure, depending on a number of factors and variables such as the level of skills, the type of work, the task content, the intensity of ICT use and workers' gender and household composition.
Keywords: 330; Telework; Covid-19; Italy; Work organisation; Job quality; Work-life balance